Peramalan Produksi Beras di Provinsi Jawa Tengah - Muhammad Ridwan; Hari Purnomo; Nancy Oktyajati (Program Studi Teknik Industri Universitas Setia Budi, 2021)
The availability of local rice needs to be predicted to meet the demand for rice supply in Indonesia. Central Java, as the third largest rice producer in Indonesia, is one of the pillars of national rice demand. The amount of food production in Indonesia is an important factor in determining the right food supply. Forecasting rice production in Central Java is necessary to determine future food conditions. The purpose of this research is to develop a forecast model for rice production in Central Java province and to find out the estimated rice production in Central Java Province in the next 5 years. The time series forecasting method was used in this study. The data used in this study are data on rice production from 1993 to 2020. From the results of the Auto Correlation Function (ACF) test, it is known that the production data has a trend data pattern. The method used in this study is the double exponential smoothing method with two parameters (Holt's Methods). The optimal forecasting model is obtained with the help of solver software in Microsoft Excel. By using the help of the Microsoft Excel solver, the optimal constant value α is 0,767 and β is 0,412 with a Mean Absolute Precentage Error value of 4,82%. Forecasting results from 2021 to 2025 are known to decline every year. The average decline in rice production in the next 5 years is estimated at 4,4% per year. Keywords: rice, exponential smoothing, Central Java, forecasting